Damping Subsynchronous Resonance in Dynamic Phasor and dq0 model using Thyristor Controlled Reactor - Siddh, M.G (International Journal of Computer Sciences and Engineering, 2019)
This paper presents the use of a Thyristor controlled reactor with local signal to mitigate subsynchronous resonance in a power system. The dynamic phasor base model and dq0 model of two area power system is considered in this paper. Modal speed deviation is used as local signal in both models. This local signal modulates the firing angle of TCR through PI controller in dynamic phasor base model and dq0 model of power system . This paper shows that the designing parameter of PI controller and mitigation behaviour of SSR using local signal in dynamic phasor based model and dq0 model closely match with each other.